Unilateral Hypoglossal Nerve Palsy as a COVID-19 Sequel. (December 2020) - Costa Martins, Daniela; Branco Ribeiro, Sofia; Jesus Pereira, Isabel; Mestre, Susana; Rios, Jonathan
Abstract : Abstract: Coronavirus disease 2019, caused by severe acute respiratory syndrome coronavirus 2 is spreading around the world, and the outbreak continues to escalate. Recently, it has been noticed that besides the typical respiratory complications, some severely affected coronavirus disease 2019 patients also experience neurological manifestations. Here, we describe the case of a newly diagnosed unilateral hypoglossal nerve palsy in a severe coronavirus disease 2019 patient. The intubation procedure was uneventful, and magnetic resonance imaging excluded the most reported causes of isolated hypoglossal nerve injury. This case reports a rare condition. Although a reasonable doubt remains, it cannot be excluded that it may be a neurological manifestation of severe acute respiratory syndrome coronavirus 2, the authors believe it to be the cause of the palsy. The main importance of this article is to alert clinicians for neurological sequels that may require a targeted rehabilitation program. Abstract : A newly case of unilateral HNP in a severe COVID-19 patient, which may be a new neurologic manifestation of SARS-CoV-2 infection.Supplemental digital content is available in the text.